Nature and functions of an Irish money market - Hoare, Thomas F. (Statistical and Social Inquiry Society of Ireland, 1970)
The development of an economy can be usefully regarded as having two aspects. The first is the production and allocation of goods and services and the second is the emergence of a financial system. The financial structure consists essentially of rights or claims, and of the institutions which record and manage those claims. This accounting function and the related expertise of devising claims to suit the varying needs of savers and investors are the unique contributions which financial institutions make to the functioning of a developed economy.
Read before the Society, 5 December 1969
Keywords: Irish money market; Irish financial institutions; Irish financial system; 314.15